Combination of Classical Cipher with Stream Cipher for Improving Data Security - Fairouz Mushtaq Sher Ali (Al-Qadisiyah Journal of Pure Science, 2017)
Cryptography plays an important role in providing security to data transmitted over the internetwork.This paper will present a perspective on new combinations techniques for encryption purpose, these techniques include proposing an encryption algorithm that combines the classical ciphers with moderns ciphers methods to enhance the security of ciphering process because ciphers based on just classical methods are not secure. The plaintext message to be transmitted is encrypted by combining: Caesar Substitutions method or Columnar Transpositions method with stream cipher. Thus, the intruder is unaware of the received encrypted text.When applying the proposed algorithm, we see that combination of Classical with Modern cipher have a high degree of security compared with traditional combination one, (Substitution with Transposition), because the Stream cipher relatively regard as unbreakable method, and bit-oriented method (instead of character-oriented) where the plaintext, ciphertext and the key are strings of bits.